The role of information communication technology policies in economic development: A comparison of select Asian countries - Francis Pereira (International Telecommunications Society (ITS), 2014)
While the role of telecommunication networks historically, and today broadband and the Internet, have been theoretically linked to economic growth, the empirical results have been mixed, giving rise again to the 'productivity paradox.' Many governments, particularly those in Southeast Asia, have adopted aggressive policies to deploy broadband networks and to encourage the use of these applications. These, governments are motivated to promote broadband adoption in order to realize both economic and social benefits. This paper argues that countries (or territories), specifically, Korean, Singapore and Hong Kong have been able to realize these because of the comprehensive and aggressive policies pursued by these governments. There is some evidence to suggest that these governmental policies have been successful in achieving their stated goals.
Keywords: 330; Broadband; National Information Infrastructure Policies; Foreign direct Investment